Green Marketing: integrated social and environmental responsibility in the marketing environment - Dalmoro, Marlon; Venturini, Jonas Cardona; Diniz Pereira, Breno Augusto (Review of Business Management, 2009)
This study aims to describe and analyze as social and environmental responsibility is integrated in the marketing strategy of a Coca-Cola Company franchisee. By the perceptions of Karna, Hansen and Juslin (2001), environment marketing is described based on three hierarchical levels: strategic, structural and functional marketing. There has been developed a qualitative approach through case study, in which the data were collected through semi-structured interviews with people involved in the process of environmental and social management of the franchisee company. Data treatment was used in the analysis of content. In the interviewer’s perception, the company is in advanced process of integration across the organization of a green marketing culture, primarily by the relationship of the franchisee maintained with the Coca-Cola Company. It is observed that the franchisee enterprise as the company, in general, are in a pro-active situation in green marketing terms, even if the institutional environment does not comply with its fullest role. Key words: Green marketing. Environmental management. Social responsibility. Environmental responsibility.